The Effect of Community Plantation Development to the Empowerment and the Investment Forest Village Community - Sari Silaban, Dheva; ., Saharudin (Sodality: Jurnal Sosiologi Pedesaan, 2015)
Community Plantation (not incorporated) are plantations held or managed by planters for small businesses grouped in smallholder tree crops and plantation household business people. In its management, smallholder plantations can affect the level of empowerment and investment communities working on forest villages. The purpose of this study is to analyze the role of government in encouraging or influencing the empowerment of farmers to invest in plantations. The approach used to analyze the effect is the quantitative approach with survey method that is supported by the relevant qualitative data. The results showed the level of government’s role does not affect the level of empowerment of forest villagers. However, the level of the role of government affect the rate of integration of commodity farm forest villagers. At the level of investment, the implementation of people’s plantation management does not affect the level of community investment significantly.Keywords: role of governments,forest villagers, integration